Interconnections and interdependencies of economic development and shadow banking sector in developing and transitional economies - Liang, Yao; Jin, Xu; Azimzadeh, Aslan Javid (Technological and Economic Development of Economy, 2024)
The research objective is defined as the identification and confirmation of empirical relationships between shadow banking activities and economic development in developing and transitional economies to establish a theoretical basis for minimizing potential risks associated with shadow banking. The methodological design is based on a quantitative approach, implemented through correlation-regression analysis and ARIMA forecasting methods. The research findings confirm Hypothesis 1: China’s shadow banking is closely interconnected with the country’s economic development. However, Hypothesis 2 (the reduction of shadow banking in China contributes to per capita GDP growth) is only supported for specific structural elements of shadow banking that contribute to economic overheating. In contrast, for other structural elements, such as entrusted loans, a strong direct correlation exists, promoting a positive impact of shadow banking on the country’s economic development. This highlights the need for a highly balanced state policy to minimize shadow banking risks. The research results can be valuable for professionals in public administration and academic researchers, particularly in terms of shaping future research directions.